Análisis del hábitat del jaguar (Panthera onca, Carnivora: Felidae) en la península de Osa, Costa Rica: una perspectiva de paisaje - Sandoval Hernández, Iván (2013)
We made a Landscape analysis of the jaguar habitat (Panthera onca) at the Osa Peninsula (OP), Costa Rica. We quantified the value of ecological variables (forest coverage, jaguar records, terrain roughness and presence of water), spatial variables (size, shape, exposition, fragmentation and isolation between fragments) and anthropogenic variables (number of houses and ranches). We created a grid of 90 cells (25 km2). It was found that forest is the most abundant type of coverage (115 037 ha, 73% of total area). 69% (71 jaguar records) were recorded in the Corcovado National Park (CNP), 31% (32 records) in the Golfo Dulce Forest Reserve (GDFR). With respect to spatial variables forest fragments are located in larger cells at to the CNP, outside of it, fragments are small and with irregular shapes. Forests tend to fractals shapes (fractal dimension: 1.4), are exposed to edge effects (Patton compaction index: 0037-0087) and are isolated (average distance between forest fragments was 290m). In addition, the forest coverage in the vicinity of forest areas is heterogeneous (juxtaposition index: 58.2). Regarding anthropogenic variables, protected areas had 124 139 Ha (79%, the study area), ranches are abundant outside the national parks (up to 34 farms per cell). The number of houses outside the national parks varied from 46-645 per cell. It was determined that percentage of forest cover was the only variable who explained the presence of the jaguar in the OP (X2: 3.23, P = 0.08) and it was found that by decreasing the amount of forest decreases the number of jaguar records.